An infant with an extremely rare cobalamin disorder: Methionine synthase deficiency and importance of early diagnosis and treatment - Kasapkara, Çiğdem Seher; Yılmaz-Keskin, Ebru; Özbay-Hoşnut, Ferda; Akçaboy, Meltem; Polat, Emine; Olgaç, Asburçe; Zorlu, Pelin (The Turkish Journal of Pediatrics, 2019)
Functional methionine synthase deficiency can be separated into two classes, cobalamin (Cbl) deficiency type E (CblE) and type G (CblG), which are the result of mutations that affect methionine synthase reductase or methionine synthase, respectively. Deficiency of methionine synthase activity may result in megaloblastic anemia without methylmalonic aciduria and neuromuscular abnormality of varying severity. Delayed milestones, ataxia, cerebral atrophy, muscular hypotonia, neonatal seizures, and blindness have been reported as the associated clinical findings. Early diagnosis and treatment are crucial for a more favorable diagnosis of the affected cases. Herein we report a three-month-old boy with CblG disease who presented with failure to thrive, chronic diarrhea, feeding intolerance, oral ulcers, microcephaly and hypotonia, and showed a dramatic response to treatment. In the first few months of life, megaloblastic anemia accompanied by apparent neurological involvement should direct physicians to order examinations like measurement of total homocysteine and methylmalonic acid levels to detect possible forms of inherited Cbl intracellular metabolism disorders.
Keywords: cobalamin; homocysteine; megaloblastic anemia; methionine